The Relationship Knowledge of Pregnant Women With the Utilization of Antenatal Care (ANC) Services in Panombeian Panei Health Center Simalungun Regency - Sondang Sidabutar; Rina Valensia; Novita Sinaga (PT Inovasi Pratama Internasional, 2023)
Antenatal Care (ANC) is a service provided to pregnant women on a regular basis to maintain the health of the mother and her fetus. This includes prenatal checks and efforts to correct deviations found, providing basic interventions as well as educating and motivating mothers so they can take care of their pregnancies and prepare for their deliveries. ANC services are health services carried out by health workers to mothers during their pregnancy according to established standard of antenatal care. This ANC service is obtained at least 4 times during pregnancy, namely 1 time in the first and second trimesters, 2 times in the third trimester. Ideally, pregnant women get ANC services 12 to 13 times, namely every month in the first and third trimesters. At 28 to 32 weeks of gestation 2 times and 4 visits at 36 weeks of gestation (Prawiroharjdo, 2010). The purpose of this study was to determine the relationship between knowledge of pregnant women and the use of antenatal care (ANC) at the Panombeian Panei Health Center, Simalungun Regency in 2017. This type of research was analytic with a cross-sectional approach. The population of this study were pregnant women who came to visit the Panei Appearance Health Center. monthly average of 40 people. The sample in this study were all pregnant women (total sampling). The results of the study are based on the results of the Chi-Sguare statistical test. There is a relationship between Knowledge and Utilization of Internal Care Services (ANC) at the Panombeian Panei Health Center, Simalungun Regency, in 2017. The results obtained from the Chi-Sguare statistical test obtained a p value of 0.004 ≤ α (0.05 ).